ORIENTASI MASA DEPAN ANAK PUTUS SEKOLAH USIA PRAREMAJA DARI KELUARGA MISKIN DI RUMAH BACA UMI (RUMI) KELURAHAN SUMUR BATU KECAMATAN BANTAR GEBANG KOTA BEKASI - marwanti martina; Rahartini Purnama Asri; Abas Basuni (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2023)
This research aims to examine: 1) Description the social situation of children who are beneficiaries of Rumah Baca Umi (Rumi), 2) Future orientation of informants based on motivational dimensions, dan 3) Future orientation of informants based on cognitive representation dimensions. The method used in this research is qualitative with a case study approach. Data collection techniques in this research were carried out through participatory observation, in-depth interviews, and documentation. There were 8 informants in this research that using purposive sampling technique. The results of this research indicate that preteen school dropouts from poor families have been oriented towards the future through the goals and priorities of their chosen field, although there are still those who do not understand each aspect of the dimensions that need to be built since childhood, because that is influenced by the lack of parental roles and the subculture of children living in poor communities. Therefore, the researcher proposes a program “Parenting Workshop dalam Merajut Kasih Masa Depan Generasi (Makassi)” in an effort to solve problems and fulfill the needs of school dropouts children from poor families starting from the parents role towards the children